2024
DOI: 10.2174/2589977515666230608140606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 Vaccination on Menstrual Cycle Patterns of Reproductive-age Women: A Multi-centric Observational Study

Abstract: Aim: The study was conducted to know the impact of COVID-19 vaccination on menstrual cycle patterns and pre- and post-menstrual symptoms in women aged 18-45 years Background: COVID-19 vaccination was introduced to combat the dreadful impacts of human coronavirus infection. The two indigenously developed COVID-19 vaccines approved for use in India are COVISHILED and COVAXIN. Objectives: To investigate the effects of COVID-19 vaccination on the menstrual cycle, pre- and post-menstrual symptoms and to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The study reported that irregularities of the menstrual cycle and length were significantly higher in the COVAXIN group (7.2%) as compared to the COVISHIELD (5.3%) group. 11 Similar to this Indian study, a retrospective cohort study from Columbia, reported heavy menstrual changes in 41.8% of the respondents and irregular cycles in 42%. 12 In our study, it appears that the risk of heavier menses following covid vaccination is likely to be is 1 in 10.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The study reported that irregularities of the menstrual cycle and length were significantly higher in the COVAXIN group (7.2%) as compared to the COVISHIELD (5.3%) group. 11 Similar to this Indian study, a retrospective cohort study from Columbia, reported heavy menstrual changes in 41.8% of the respondents and irregular cycles in 42%. 12 In our study, it appears that the risk of heavier menses following covid vaccination is likely to be is 1 in 10.…”
Section: Discussionsupporting
confidence: 74%
“…10 A large multicentric observational study from India, noticed very similar patterns in menstrual changes. Kumar et al, 11 who surveyed 5709 women, reported that 5.8% of the women had menstrual changes. This study quoted that 50.2% of the respondents had excessive bleeding and 48.8% had scanty periods.…”
Section: Discussionmentioning
confidence: 99%